1981
DOI: 10.1161/01.res.49.6.1356
|View full text |Cite
|
Sign up to set email alerts
|

Studies on phosphorylation of canine cardiac sarcoplasmic reticulum by calmodulin-dependent protein kinase.

Abstract: Two endogenous protein kinase activities, cAMP-dependent and calmodulin-Ca2+-dependent, are associated with isolated cardiac sarcoplasmic reticulum (SR) vesicles. Both kinases phosphorylate an endogenous substrate of approximately 22,000 daltons (phospholamban). The phosphorylation of phospholamban by either the intrinsic or by exogenous cAMP-dependent protein kinase is found to be Ca2+-independent between 0.05 and 100 microM free Ca2+. Calmodulin-dependent phosphorylation, on the other hand, does not require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Thus, it is widely accepted that phosphorylation of PLB at Ser 16 is obligatory for Thr 17 phosphorylation and that Ser 16 phosphorylation is the dominant molecular event responsible for accelerated cardiac relaxation. However, in vitro studies in the isolated SR membranes have consistently indicated that Ser 16 and Thr 17 can be readily and independently phosphorylated by PKA and CaMKII, respectively, and that when both are phosphorylated, there is an additive interaction (20,21). The apparent discrepancy between in vivo and in vitro PLB phosphorylation is yet to be reconciled.…”
Section: Phospholamban (Plb)mentioning
confidence: 99%
“…Thus, it is widely accepted that phosphorylation of PLB at Ser 16 is obligatory for Thr 17 phosphorylation and that Ser 16 phosphorylation is the dominant molecular event responsible for accelerated cardiac relaxation. However, in vitro studies in the isolated SR membranes have consistently indicated that Ser 16 and Thr 17 can be readily and independently phosphorylated by PKA and CaMKII, respectively, and that when both are phosphorylated, there is an additive interaction (20,21). The apparent discrepancy between in vivo and in vitro PLB phosphorylation is yet to be reconciled.…”
Section: Phospholamban (Plb)mentioning
confidence: 99%
“…In vitro studies have shown that Ser 16 is phosphorylated by cAMP-dependent protein kinase, whereas Thr 17 is phosphorylated by Ca 2ϩ -calmodulin-dependent protein kinase (4). Phosphorylation of each site occurs in an independent manner, although it is not presently clear whether the stimulatory effects of the two phosphorylations on SR Ca 2ϩ transport are additive (5)(6)(7)(8)(9).…”
Section: Phospholamban (Plb)mentioning
confidence: 99%
“…In vitro experiments indicate that PKA and CaMKII phosphorylate phospholamban at two different sites, Ser 16 and Thr 17 , respectively (3). These phosphorylations are independent of each other, and when both are operating, they appear to have an additive action (4). In the intact heart, ␤-adrenergic stimulation phosphorylates phospholamban at both sites (5), which indicates that PKA-and CaMKII-dependent pathways are also working in the functioning heart.…”
Section: Cardiac Sarcoplasmic Reticulum (Sr)mentioning
confidence: 99%